"EVERY WORD YOU JUST SAID IS WRONG": ONLINE RAGE AND INCLUSIVITY IN DISNEY FRANCHISE FANDOM - Blodgett, Bridget; Salter, Anastasia (AoIR Selected Papers of Internet Research, 2018)
The months leading up to the release of Disney franchise films The Last Jedi (December 2017) and Black Panther (February 2018) were marked by speculation, concern, and fervor in equal measures from the established fan communities of Star Wars and Marvel. Both franchises have been associated with toxic geek masculinity, a performed, communal hypermasculinity marked by exclusionary practices and rhetoric (Salter & Blodgett, 2017). By centering either non-white or non-male characters as leads in roles traditionally dominated by cisgender white men, both films became centers for toxic discourse and targeted campaigns aimed at disrupting their commercial success. In this paper, we will situate these case studies as emblematic of the changing discourse of geek fandom spaces, and its intersections with white supremacy and misogyny.